Tasarrufun iptali davasının işlevi bakımından aciz vesikası ile ilişkisi hakkında düşünceler - (:unkn) unknown (My University, 2009)
0
Reflections on the relationship between insolvency certificate and the function of the suit for annulment of the disposal
Keywords: Hukuk